English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

.A fried chicken franchise finds that the demand equation for its new roast chicken product, "Roasted Rooster", is given by
p=48/ q^1.5
where p is the price (in dollars) per quarter-chicken serving and q is the number of quarter-chicken servings that can be sold per hour at this price. Express q as a function of p, and find the elasticity of demand when the price is set at $6 per serving.

2006-12-06 16:47:13 · 2 answers · asked by i 1 in Science & Mathematics Mathematics

2 answers

p * q^1.5 = 48
q^1.5 = 48 / p
q = (48 / p)^(2/3) = (48 * p^-1)^(2/3)

When p = 6,

q = 8^(2/3) = 4

As a check,

6 = 48 / 4^1.5
6 = 48 / 8

Yes!!!

BabyGirl is wrong in her third equation. She handles the 1.5 incorrectly.

The elasticity of demand at any particular price is (% Change in Quantity Demanded)/(% Change in Price).

Let us start by taking the first derivative of the demand function:

q' = (2/3)(48 * p^-1)^(-1/3) * (-48) * (p^-2)

For p = 6,

q' = (2/3) * 8^(-1/3) * (-48) * (6^-2)
= (2/3) * (1/2) * (-48) * (1/36)
= (1/3) * (-48) * (1/36)
= -16 * 1/36
= -16/36 = -4/9

This means that at p = 6, for each dollar increase in p, the quantity demanded goes down by 4/9.

Let's do a rough check on that before going on.

For p = 7,

q = (48/7)^(2/3) = 3.6, down from 4.

Close enough. Let's go on.

The % change in price is (7 - 6) / 6 = 1/6
The % change in the quanitity demanded is

(old quantity - new quantity) / old quantity
(4/9) / 4 = 1/9

The elasticity of demand is

(1/9) / (1/6) = 2/3

An elasticity of less than 1 means that as the price increases, the quantity demanded does not fall proportionately. It falls less than proportionately, leading to an increase in gross revenue.

Let's see. At p = 6, the quantity demanded was 4, for a gross revenue of 24. At p = 7, the quantity demanded is 4 - 4/9, or 32/9, leading to a gross revenue of 7 * 32/9 = 224/9 = 24.89, up from 24.

2006-12-06 16:52:08 · answer #1 · answered by ? 6 · 0 0

I'm not sure, but here goes...

q^1.5 = 48/p

1.5 ln q = ln (48/p)

q = {e^(48/p} / 1.5

When p =6

q = e^8/1.5
q' =

2006-12-07 00:59:44 · answer #2 · answered by Babygirl 3 · 0 0

fedest.com, questions and answers